THE EFFECTS OF OIL AND GOLD PRICES ON G7 COUNTRIES - Bildirici, Melike; Sonustun, Fulya Ozaksoy (ACAD ECONOMIC STUDIES, 2018)
The volatility of oil and gold prices has significant role on government's' economic policies and structures of business cycles. In this paper, it was aimed to analyze relation between gold and oil prices and their effects on the business cycle structures of the selected G7 countries. In this regard, MS-AR and MS-VAR models were selected to analyze gold and oil price volatilities, identify the business cycle structures and make effective economic policy inferences for each of the selected countries. Transition probabilities of this paper emphasize the asymmetric behavior of business cycles. More critically, economic policy results of this paper support that regime transition probabilities from modest growth to recession period is lower than transition probability from crisis regime to rapid growth stage. Besides, the findings reveal the importance of gold and oil prices on economic growth and welfare.
Keywords: Volatility of Oil and Gold Prices; MS-AR(X) analysis; MS-VAR(X) analysis; MACROECONOMY RELATIONSHIP; EXCHANGE-RATE; TIME; MARKET; HEDGE; Business & Economics; Mathematics